Two decades of risk factors and transfusion‐transmissible infections in Dutch blood donors. Issue 1 (9th September 2015) - Slot, Ed; Janssen, Mart P.; Marijt‐van der Kreek, Tanneke; Zaaijer, Hans L.; van de Laar, Thijs J.
Abstract : BACKGROUND: Risk behavior–based donor selection procedures are widely used to mitigate the risk of transfusion‐transmissible infections (TTIs), but their effectiveness is disputed in countries with low residual risks of TTIs. STUDY DESIGN AND METHODS: In 1995 to 2014, Dutch blood donors infected with hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), human T‐lymphotropic virus (HTLV), or syphilis were interviewed by trained medical counselors to identify risk factors associated with TTIs. Trends in the prevalence and incidence of TTIs were analyzed using binomial regression models. RESULTS: A total of 972 new donors and 381 repeat donors had TTIs. New donors had higher rates of TTIs compared to repeat donors. Although the HBV and HCV prevalence gradually decreased over time, the incidence of all five TTIs remained stable during the past two decades. In new donors the TTIs had the following risk profiles: "blood‐blood contact" for HCV, "unprotected sex" for HIV and syphilis, and "country of birth" for HBV and HTLV. In infected repeat donors, sexual risk factors predominated for all TTIs. At posttest counseling, 28% of infected repeat donors admitted to risk factors leading to permanent donor exclusion if revealed during the donor selection procedure (predominantly male‐to‐male sex and recent diagnosis of syphilis). CONCLUSION: The prevalence and incidence of TTIs among Dutch blood donors are six‐ to 60‐fold lower than in the general Dutch population, illustrating the effectiveness of donor selection procedures. However, at least a quarter of infected donors appeared noncompliant to the donor health questionnaire (DHQ), suggesting that DHQs, or the way donor questioning is implemented, can be improved.